The Legality of Deliberate Miranda Violations: How Two-Step National Security Interrogations Undermine Miranda and Destabilize Fifth Amendment Protections - Crain, Lee Ross (2013)
As part of the global “War on Terror,” federal agents intentionally delay issuing Miranda warnings to terrorism suspects during custodial interrogations. They delay the warnings presuming that unwarned suspects will more freely offer vital national security intelligence. After a suspect offers the information he has, agents administer Miranda warnings and attempt to elicit confessions that prosecutors can use at the suspect’s trial. No court has ruled on the constitutionality of this two-step national security interrogation process to determine whether admitting the second, warned confession is allowed under Miranda v. Arizona and its progeny. A fragmented Supreme Court examined two-step interrogations generally in Missouri v. Seibert but offered no clear holding. This Note argues that while confessions derived from two-step national security interrogations are admissible under Justice Kennedy’s Seibert test, courts should instead apply Justice Souter’s Seibert test to limit the use of such interrogations. This Note further contends that permitting two-step national security interrogations contravenes the spirit, if not the letter, of the Fifth Amendment as well as decades of Miranda jurisprudence